Liquidez e fluxo de caixa: um estudo teórico sobre alguns elementos que atuam no processo de formação do caixa e na determinação do nível de liquidez de empresas privadas não financeiras - Sá, Carlos Alexandre (2004)
There are many works addressing cash flow as an instrument of investment and project analysis. However, especially in Brazil, the literature addressing cash flow as an instrument of liquidity administration is relatively scarce. This issue is particularly relevant for, right now, among the amendments to Law 6.404/76 being considered, is the replacement of the Source and Application of Funds Statement by the Cash Flow Statement, similarly to what has happened in many other countries. This work tries to put together some of the available information concerning this issue, to deepen the existing knowledge about the mechanics of cash generation, to exploit some assumptions which have not yet been considered and to suggest a method for cash flow analysis and interpretation that will allow the managers a better knowledge of their business in order to improve their decision making processes based on cash flow.